Byzantine Coinage from the Museum of the Franciscan Monastery of St Anthony of Padua – Humac (Ljubuški, Bosnia and Herzegovina) (Archaeologia Adriatica, 2026)
The article analyses 38 Byzantine coins kept in the Museum of the Franciscan Monastery of St Anthony of Padua in Humac near Ljubuški, Bosnia and Herzegovina. Most of them have not been published so far. They reached the Humac Museum mainly as donations from priests. The earliest coins are dated to the reign of Anastasius I (491–518), while the most recent belong to the time of Manuel I Komnenos (1143–1180). The largest number of coins is attributed to the reign of Justinian I (527–565) and to the grouping of so-called anonymous folles of the 10th/11th century. Most of the coins originate from the Constantinople mint, while some specimens come from the mints of Nicomedia, Antioch, Cyzicus and Thessaloniki, along with one piece that have been struck in assumed Salonitan mint. Among the rarer specimens are a gold coin of Constantine IV (668–685) and a silver coin of Leo VI (886–912). The collection also contains two gold coins of Romanos III Argyros (1028–1034). While exact findspots for the coins are unknown, it can reasonably be assumed that these were in Herzegovina, more precisely from the territory of the Herzegovinian Franciscan Province.
Keywords: Herzegovina; Ljubuški; the Museum of the Franciscan Monastary of St Anthony of Padua Humac; Byzantine numismatics; Byzantine coins; gold coins of Romanos III Argyros